2022
DOI: 10.33919/esnbu.22.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Undergraduate Students’ Attitudes Towards Learning English Based on Academic Major, Class Level, and Gender Variables

Abstract: The goal of this study is to investigate undergraduate students' attitudes toward learning English based on their academic major, class level, and gender. A total of 150 undergraduate students (65 males and 85 females) distributed in different class levels and different colleges and departments were surveyed using a Likert-type scale. Statistical differences indicated that students had a mixed bag of attitudes about the English language, with some being positive and others being negative. The findings revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Almost 57.50% of the students either strongly disagreed or disagreed with item number II.11. This result is in line with previous studies which indicated that the number of interlocutors affected the students' communication competence (Andika et al ., 2022; Azwar et al ., 2021) and that public speaking activities are among the most challenging tasks in and outside the classroom settings (Subekti, 2018a, b). The students felt insecure speaking in front of others as they risk losing face and having their peers judge them negatively (Horwitz et al ., 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 57.50% of the students either strongly disagreed or disagreed with item number II.11. This result is in line with previous studies which indicated that the number of interlocutors affected the students' communication competence (Andika et al ., 2022; Azwar et al ., 2021) and that public speaking activities are among the most challenging tasks in and outside the classroom settings (Subekti, 2018a, b). The students felt insecure speaking in front of others as they risk losing face and having their peers judge them negatively (Horwitz et al ., 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Communication is also crucial as it allows graduates to communicate with people in the target language. Motivated students could be more eager and excited to devote time to studying a language and participate in academic activities (Muftah, 2022b; Muftah and Rafik-Galea, 2013). However, being able to speak with someone in a target language is insufficient if that person is unwilling to establish a target language communication (Azizi and Farid Khafaga, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that females generally outperform males in English language skills and have higher motivation and attitudes towards learning English (AlJuhani, 2023; nurlindawati, Yasin, & Hadi, 2022; Sabiq, Arwi, Khusna, Adifia, & Nada, 2021). However, when it comes to the frequency of English use outside of school, there is no significant difference between male and female students (Muftah, 2022). While males may exhibit higher levels of anxiety related to English learning (Du, 2023), both genders generally show moderately high attitudes and motivation towards English, with females often scoring higher on surveys.…”
Section: Gender Differences In English Language Skills English Use Ou...mentioning
confidence: 99%